Impact of thermal processing on the nutrients, phytochemicals, and metal contaminants in edible algae. Issue 2 (31st December 2021) - Ho, Kacie K. H. Y.; Redan, Benjamin W.
Abstract: Edible algae products have increasingly become a larger component of diets worldwide. Algae can be a source of essential micronutrients and bioactive phytochemicals, although select varieties also often contain elevated concentrations of heavy metal contaminants. Due to the effects thermal processing of foodstuffs can have on levels of nutrients, phytochemicals, and contaminants, it is important to consider the role processing has on the levels of these components in algae food products. Here, we evaluate the literature covering how different types of processing, including commercial thermal application and in-home preparation, affect constituents such as vitamins, minerals, carotenoids, pigment compounds, and metal contaminants. Overall, the literature suggests that there are optimum processing conditions and specific cooking techniques that can be used to increase retention of important nutritional components while also reducing concentrations of metal contaminants. Although further research is needed on how thermal processing affects individual compounds in algae and their ultimate bioavailability, these data should be taken into consideration in order to inform design of product processing to both increase retention of nutritional components and limit metal contaminants.